2009
DOI: 10.1177/0037549709348801
|View full text |Cite
|
Sign up to set email alerts
|

An Advanced System for Supporting the Decision Process within Large-scale Retail Stores

Abstract: This paper proposes an advanced decision system, called Virtual Dynamic Store (VDS), for supporting retail store management. The VDS architecture supports the decision processes within retail stores by providing users with three main functionalities: store layout analysis, item and shelf management, and store monitoring and control by real-time simulation (or remote control by on-line simulation). As additional functionality, not related to the decision process within a retail store, the VDS architecture could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 32 publications
(32 reference statements)
0
18
0
Order By: Relevance
“…There are many recent studies concerning supply chain models (De Sensi et al 2008, Bruzzone and Longo 2009, Buil et al 2010, Wadhwa et al 2010. Many studies are based on simulation modelling, which is an effective way to test policies and operational rules.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are many recent studies concerning supply chain models (De Sensi et al 2008, Bruzzone and Longo 2009, Buil et al 2010, Wadhwa et al 2010. Many studies are based on simulation modelling, which is an effective way to test policies and operational rules.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other research studies on warehouse dimensioning can be found in Pliskin and Dori (1982), Azadivar (1989) and Heragu et al (2005). A specific study (also focused on warehouse department dimensioning in a retail store) using advanced 3D simulation tools and artificial intelligence techniques is proposed by Bruzzone and Longo (2010 Moder and Thornton (1965) focus on different ways of stacking pallets within a warehouse. Berry (1968) discusses the tradeoffs between storage efficiency and material handling costs through analytic models.…”
Section: Internal Logistics: a Survey On Warehouse Managementmentioning
confidence: 99%
“…A significant number of systems of technological, social, or financial interest may present a high degree of complexity in their composition, in the interrelation among their components, in their behavior, or in all of these features [1,2]. Many of these systems can be considered as discrete event systems (DES) [3,4], such as manufacturing facilities, food industry, supply chains, airports, or traffic networks [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%